TEACHER CORRECTIVE FEEDBACK IN TEACHING DESCRIPTIVE TEXT WRITING OF ENGLISH FOR SPECIFIC PURPOSES: A CASE STUDY - Alfayed, Affied; Hartiningsih, Sri; Hamdani, Muhammad Fadhil (Premise: Journal of English Education and Applied Linguistics, 2024)
The demand for vocational education in Indonesia is rising due to the evolving and fiercely competitive job market. English teachers are required to be able to improve students' English skills for specific purposes, mainly writing skills. Few studies have investigated how teachers provide corrective feedback on students' writing in English for Specific Purposes (ESP) settings. Therefore, this study investigates teachers' practice of corrective feedback and the rationale behind the practice in ESP settings. This research used a case study method on an English teacher in a secondary vocational school. Interviews, classroom observations, and documentation of student writing were used to collect data. The findings revealed that the teacher practiced oral corrective feedback when teaching the writing of a product description text. The oral corrective feedback strategies the teacher practices include explicit correction, metalinguistic correction, and recast. Additionally, the reason behind the practice is based on the teacher's teaching experience and personal beliefs. This study implies that teachers should consider students' developmental levels, linguistic needs, and feelings when using oral corrective feedback in ESP.